2007
DOI: 10.1002/adma.200701582
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Amplified Stimulated Emission from CdSe‐CdS‐ZnS Quantum Dot Doped Waveguides with Two‐Photon Infrared Optical Pumping

Abstract: In principle, a population inversion in semiconductor quantum\ud dots can be achieved through electrical, chemical or optical\ud pumping. To date however, it has only been successfully\ud demonstrated with optical pumping in the 1-photon absorption\ud range (i.e., above the semiconductor bandgap). Under\ud these conditions amplified stimulated emission (ASE) in 1-D\ud waveguides and lasing within microsphere cavities and distributed\ud feedback structures has been observed. In these studies,\ud it was demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(123 citation statements)
references
References 30 publications
6
114
2
Order By: Relevance
“…A narrowing of the emission profi le from ∼ 38 nm to ∼ 11 nm is readily observed at higher pump powers, signifying the onset of ASE. A low threshold of ∼ 68 μ J cm − 2 was derived from a plot of the integrated PL intensity against pump power as depicted in Figure 2 (b), which is 5 and 50 times lower than the best ASE thresholds previously reported in CdSe/CdS/ ZnS based zirconia fi lms, [ 15 ] and CdS/ZnS based silica fi lms [ 6 ] respectively. It is possible that further reduction in the threshold may be achieved using state-resolved optical pumping, which was demonstrated recently in CdSe NC-based fi lms.…”
Section: Doi: 101002/adma201200121mentioning
confidence: 65%
“…A narrowing of the emission profi le from ∼ 38 nm to ∼ 11 nm is readily observed at higher pump powers, signifying the onset of ASE. A low threshold of ∼ 68 μ J cm − 2 was derived from a plot of the integrated PL intensity against pump power as depicted in Figure 2 (b), which is 5 and 50 times lower than the best ASE thresholds previously reported in CdSe/CdS/ ZnS based zirconia fi lms, [ 15 ] and CdS/ZnS based silica fi lms [ 6 ] respectively. It is possible that further reduction in the threshold may be achieved using state-resolved optical pumping, which was demonstrated recently in CdSe NC-based fi lms.…”
Section: Doi: 101002/adma201200121mentioning
confidence: 65%
“…This is because TiO 2 -QD nanocomposite formed a type II heterostructure where electrons can scape through the matrix, while the ZrO 2 -QD interface resulted in a type I heterostructure where carriers are strongly confined in the QD. Again, Jasieniak et al [55] demonstrated ASE at different wavelengths (547, 573, 604 and 625 nm) by incorporating multishell CdSe/CdS/ZnS QDs in a ZrO 2 matrix. Thresholds between 0.15 mJ/cm 2 (625 nm) and 1.4 mJ/cm 2 (547 nm) under femtosecond excitation were obtained.…”
Section: Sol Gel Nanocompositesmentioning
confidence: 99%
“…Indeed, it is even possible to demonstrate ASE under two photon pumping in colloidal nanoparticles. First studies were developed by Jasieniak et al by incorporating CdSe-CdS-ZnS QDs in ZrO 2 matrices [55]. Authors compared the generation of gain under one (excitation wavelength at 400 nm) and two photon (excitation wavelength at 800 nm) pumping in nanocrystals of different sizes.…”
Section: -P9mentioning
confidence: 99%
“…[28] This hybrid system possesses a high refractive index and retains high photostability under one-and two-photon pumping, important peculiarities for developing QD-based DFB lasers. [29] Thin films of densely packed CdSe-CdZnS-ZnS QDs in a zirconia host were deposited, by spin-coating, onto quartz substrates. A comparison of the absorption and emission properties of the QDs dispersed in EtOH and QD/ZrO 2 thin films wileyonlinelibrary.comrange the transient signal of the first absorption band is dominated by bleaching.…”
Section: Linear and Nonlinear Absorption Characteristicsmentioning
confidence: 99%